Trigger mechanism and dynamic causes of the Taiwan earthquake sequence on September 17, 2022 - HUANG Shaohua; WAN Yongge; FENG Gan; LI Xiao; GUAN Zhaoxuan (Dizhi lixue xuebao, 2023)
On September 17th and 18th, 2022, two earthquakes struck Taiwan Province of China in Taitung County and Hualien County, respectively, measuring MS6.5 and MS6.9 in magnitude, followed by multiple aftershocks. Both seismic events were situated along the Longitudinal Valley Fault and exhibited a reverse strike-slip mechanism. The geological setting in this area is intricate, as the Longitudinal Valley Fault zone represents a subduction zone where the late Mesozoic Paleo-Pacific plate converges with the East Asian continental margin, resulting in a predominant thrust-type tectonic stress background. However, historical earthquake data in this region have indicated a prevalence of reverse-faulting earthquakes. To address the causes of these reverse strike-slip fault earthquakes and their relationship with the tectonic stress field in the area, we first reconstructed the tectonic stress field by analyzing the focal mechanisms of past earthquakes within the study area. The resulting stress field was characterized by compressive stress oriented with an azimuth of NWW. Subsequently, this stress field was projected onto fault planes with various strike and dip angles. This analysis revealed that certain fault joints experienced more significant relative shear stress and lower relative normal stress, suggesting that these joints were more prone to dislocation, leading to earthquakes of the reverse fault type, reverse strike-slip type, and strike-slip type. Furthermore, the proximity and timing of the two earthquakes within a two-day span prompted an examination of their potential triggering relationship. Researchers calculated the Coulomb rupture stress changes caused by the MS6.5 earthquake on the rupture plane of the MS6.9 earthquake and its sliding direction. Their analysis indicated an increase of approximately 0.02 MPa in Coulomb rupture stress, suggesting that the Taitung MS6.5 earthquake may have triggered the Hualien MS6.9 earthquake. This study holds significant importance for understanding the seismogenic mechanism of the Longitudinal Valley Fault and gaining insights into the geodynamics of the study region.